2023
DOI: 10.36834/cmej.74411
|View full text |Cite
|
Sign up to set email alerts
|

A scoping review for designing a disability curriculum and its impact for medical students

Abstract: Background: There is an increasing need for a standardized undergraduate disability curriculum for medical students to better equip students with the proper training, knowledge, and skills to provide holistic care for individuals with disabilities. Objectives: The aim of this scoping review was to better understand and analyze the current body of literature focusing on best practice for including disability curricula and its impact on undergraduate medical students Results: Three major components for designing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
(187 reference statements)
0
3
0
Order By: Relevance
“…Using NIH’s 12-point checklist for quality of pre-post studies without controls, we estimate having met ~ 6–8 of listed evaluation strengths, including: clear study question, pre-specified eligibility, sample representativeness, pre-specified outcomes and statistical analysis of pre-post change [ 31 ]. Further, partnering with PWIDDs in the design and implementation of our multi-modal curriculum aligns with recommendations from reviews of prior curricula [ 7 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Using NIH’s 12-point checklist for quality of pre-post studies without controls, we estimate having met ~ 6–8 of listed evaluation strengths, including: clear study question, pre-specified eligibility, sample representativeness, pre-specified outcomes and statistical analysis of pre-post change [ 31 ]. Further, partnering with PWIDDs in the design and implementation of our multi-modal curriculum aligns with recommendations from reviews of prior curricula [ 7 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…A scoping review for designing a disability curriculum and its impact for medical students by Ali et al 12 reviewed existing literature on best practices for including disability curricula in undergraduate medical education. The results showed that exposing medical students to a disability curriculum improved their empathy and overall perceptions of patients with disabilities.…”
Section: Reviews Theoretical Papers and Meta-analysismentioning
confidence: 99%
“…One scoping review enumerated teaching strategies effective in educating medical students about disability including presentations, group sessions, lectures, workshops, presentations by guest lectures, online modules, and seminars ( 16 ). A survey of 14 medical schools found that most curricula that addressed disability competency had limited engagement with people with disabilities ( 17 ).…”
Section: Introductionmentioning
confidence: 99%